Astragaloside IV Attenuated 3,4-Benzopyrene-Induced Abdominal Aortic Aneurysm by Ameliorating Macrophage-Mediated Inflammation - Wang, Jiaoni; Zhou, Yingying; Wu, Shaoze; Huang, Kaiyu; Thapa, Saroj; Tao, Luyuan; Wang, Jie; Shen, Yigen; Wang, Jinsheng; Xue, Yangjing; Ji, Kangting (Frontiers in Pharmacology, 2018)
Abdominal aortic aneurysm (AAA), characterized by macrophage infiltration-mediated inflammation and oxidative stress, is a potentially fatal disease. Astragaloside IV (AS-IV) has been acknowledged to exhibit antioxidant and anti-inflammatory properties. This study was designed to investigate the protective effect of AS-IV against AAA formation induced by 3,4-benzopyrene (Bap) and angiotensin II (Ang II), and to explore probable mechanisms. Results showed that AS-IV decreased AAA formation, and reduced macrophage infiltration and expression of matrix metalloproteinase. Furthermore, AS-IV abrogated Bap/Ang II-induced NF-κB activation and oxidative stress. In vitro, AS-IV inhibition of macrophage activation and NF-κB was correlated with increased phosphorylation of AKT. Together, our findings suggest that AS-IV has potential as an intervention in the formation of AAA.